(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article illustrates the methods and technologies for the formation of special competencies of students inside lessons of modern technologies of passenger transportation. The lessons focus on developing the quality of education through the systematic use of innovative methods and technologies, the formation of special competencies between students.